2022
DOI: 10.5194/hess-26-3021-2022
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural intensification vs. climate change: what drives long-term changes in sediment load?

Abstract: Abstract. Climate change and agricultural intensification are expected to increase soil erosion and sediment production from arable land in many regions. However, to date, most studies have been based on short-term monitoring and/or modeling, making it difficult to assess their reliability in terms of estimating long-term changes. We present the results of a unique data set consisting of measurements of sediment loads from a 60 ha catchment – the Hydrological Open Air Laboratory (HOAL) – in Petzenkirchen, Aust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…When surface runoff, sediment and structural connectivities are to be investigated, and event‐based soil loss is of interest, models from the (R)USLE family are therefore not the obvious choice among available erosion models. The total sediment yield of a catchment area is frequently dominated by only a few extreme events, as lined out by Edwards and Owens (1991), Boardman (2006), González‐Hidalgo et al (2009), Gonzalez‐Hidalgo et al (2012) or Wang et al (2022), so we assume that concentrating modelling efforts on these events is a feasible approach. For example, the main cropping regions in Austria, these events mainly occur when the soil is not covered and therefore most prone to soil loss, right after seedbed preparation in spring and early summer (Klik & Eitzinger, 2010; Strauss et al, 1995; Strohmeier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…When surface runoff, sediment and structural connectivities are to be investigated, and event‐based soil loss is of interest, models from the (R)USLE family are therefore not the obvious choice among available erosion models. The total sediment yield of a catchment area is frequently dominated by only a few extreme events, as lined out by Edwards and Owens (1991), Boardman (2006), González‐Hidalgo et al (2009), Gonzalez‐Hidalgo et al (2012) or Wang et al (2022), so we assume that concentrating modelling efforts on these events is a feasible approach. For example, the main cropping regions in Austria, these events mainly occur when the soil is not covered and therefore most prone to soil loss, right after seedbed preparation in spring and early summer (Klik & Eitzinger, 2010; Strauss et al, 1995; Strohmeier et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Local factors which include topography, river control structures, soil and water conservation measures, tree cover, landuse or land disturbance such as agriculture and mining influence sediment loads in rivers [21]. Further, climate change is influencing sediment loads of rivers around the world due to changes in sediment yields as a result of climate change and associated changes in rainfall and runoff [22]. Effects of climate change in sediment yield may also interact with other anthropogenic causes of sedimentation in rivers, such as agricultural production [23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (2022) shows how Land Use Land Cover (LULC) and land structure changes are responsible for explaining the long term changes in soil erosion and sediment loads rather than climate change in the Hydrological Open Air Laboratory (HOAL) catchment, Austria. Li et al (2019) also found out that livestock grazing accelerated soil erosion more than climate change on the Qinghai-Tibet Plateau leading to increased sediment deposition.…”
mentioning
confidence: 99%